Identification of phytoconstituents from the aerial parts of Aphanamixis polystachya and evaluation of their anticancer activities - Gaja Swarna Kumari; Bandi Siva; Shainy Sambyal; Karthik Gourishetti; H.M. Sampath Kumar; Andugulapati Sai Balaji; Vaikundamoorthy Ramalingam; K Suresh Babu (Elsevier, 2022)
In continuation of our efforts in exploration of Indian flora for development of new natural product-based therapeutics, the bio-activity directed investigation of Aphanamixis polystachya led to the isolation of nineteen compounds (1-19). The structures of isolates were confirmed by interpretation of spectral studies (NMR and Mass). Among the isolates, nine compounds such as Piscidinol A (2), 24-Epipiscidinol A (3), Toonamicrocarpavarin (4), Kumuquassin E (5), Bourjotinolone A (6), Niloticin (7), Dihydromacaticadienonic acid (8), Hispidol A (9), and Bourjotinoline B (10) are reported first time from A. polystachya. All the isolates were screened for their potentials against panel of cancer cell lines and results indicated that compounds 16 and 17 showed excellent cytotoxic activity against prostate cancer with IC50 value of 7.44 ± 0.34 and 6.70 ± 1.93 µM, respectively. Further, cell cycle analysis experiments indicated that the compounds 16 and 17 induced necrosis in DU145 cells by arresting the cell cycle at S phase. In conclusion, findings of these study indicate the aerial parts of the A. polystachya have good source of anticancer drugs.